THE ROLE OF BEHAVIORAL ECONOMICS IN CONSUMER DECISION-MAKING - Asilbek Usmanov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This paper aims to analyze how behavioral economics theories and practices play an importantl role on consumption and consumer choice behavior. Behavioral economics main purpose is to obtain deeper understanding of human behavior and interactions, also to understand how they interact both as individuals and as a group. Moreover, by observing how an individual chose its precious time, income or even assets we can assume how that individual shall make the choices. Among many important theories of behavioral economics, prospect theory and its loss and gains aspects are mostly and widely studied, thus applied aspects on consumption. Prospect theory show that individuals are loss-averse, hence they more dislike losses rather than counterpart gains, therefore they are more willing to take risks to avoid a loss. Consumer behaviors towards losses or gains may also lead towards endowment effect an attachment feeling towards valuing and paying higher price for an item that is already in possession, rather than owning a new one (Thaler, 1980) . In behavioral economics consumer choice is influenced also by mental accounting, where according to Thaler (1985) is used as a cognitive bookkeeping tool that consumers use in order to keep records of financial activities and to control consumption. Application of behavioral economics theories and examples illustrated in this paper aimto show that BE and its principles have been applied in many consumption and consumer choice domains like product choice and product value, consumer spending and behavior.